A self-powered and high-frequency vibration sensor with layer-powder-layer structure for structural health monitoring. (December 2021) - Lin, Zhiwei; Sun, Chenchen; Liu, Wencai; Fan, Endong; Zhang, Gaoqiang; Tan, Xulong; Shen, Ziying; Qiu, Jing; Yang, Jin
Abstract: Vibration sensors greatly benefit medical and healthcare monitoring, environmental monitoring, and structural health monitoring. However, most of them are shadowed by relatively low-frequency vibration response, the narrow operating frequency range, and operational complexity, which hinders their use in wide practical applications. Here, we report a self-powered broadband vibration sensor with a layer-powder-layer structure based on a triboelectric nanogenerator. The internal polytetrafluoroethylene (PTFE) and silver (Ag) micro powder can vibrate under the external vibration stimuli, offering distinct advantages for high-frequency vibration sensing. The high-frequency triboelectric vibration sensor exhibits a significantly broad frequency response range of 3–133 kHz. The highest response frequency is approximately 1–3 orders of magnitude higher than most previously reported triboelectric vibration sensors. Additionally, the HVS shows directional independence, a good frequency resolution of 0.01 kHz, and small hysteresis. With these capabilities, the HVS was demonstrated in burst vibration detection, rail track fracture detection, automobile engine monitoring, and geological exploration applications. The facile and effective vibration monitoring system based on the HVS can provide a platform for various vibration monitoring applications. The self-powered high-frequency vibration sensor is a promising candidate for next-generation vibration sensors. Graphical Abstract: Vibration sensors are highly desirable in various fields, such as structural health monitoring and environmental monitoring. In this study, a self-powered high-frequency vibration sensor (HVS) is developed. The optimal HVS features a broad vibration frequency response range of 3–133 kHz, omnidirectional response, and good frequency resolution ability. The HVS was demonstrated in rail track fracture detection, automobile engine monitoring, and geological exploration applications. The HVS is a promising alternative to commercial piezoelectric vibration sensors for wide applications. ga1 Highlights: A sensor with high-frequency vibration response-ability and a broad operating frequency range is developed. The sensor shows an omnidirectional response, a good frequency resolution of 0.01 kHz, and small hysteresis. The sensor is demonstrated in rail track fracture detection, automobile engine monitoring, and geological exploration.